Molecular profiling in muscle‐invasive bladder cancer: more than the sum of its parts. Issue 5 (20th February 2019) - Sjödahl, Gottfrid; Jackson, Chelsea L; Bartlett, John MS; Siemens, D Robert; Berman, David M
Abstract: Bladder cancers are biologically and clinically heterogeneous. Recent large‐scale transcriptomic profiling studies focusing on life‐threatening muscle‐invasive cases have demonstrated a small number of molecularly distinct clusters that largely explain their heterogeneity. Similar to breast cancer, these clusters reflect intrinsic urothelial cell‐type differentiation programs, including those with luminal and basal cell characteristics. Also like breast cancer, each cell‐based subtype demonstrates a distinct profile with regard to its prognosis and its expression of therapeutic targets. Indeed, a number of studies suggest subtype‐specific differential responses to cytotoxic chemotherapy and to therapies that inhibit a number of targets, including growth factors (EGFR, ERBB2, FGFR) and immune checkpoint (PD1, PDL1) inhibitors. Despite burgeoning evidence for important clinical implications, subtyping has yet to enter into routine clinical practice. Here we review the conceptual basis for intrinsic cell subtyping in muscle‐invasive bladder cancer and discuss evidence behind proposed clinical uses for subtyping as a prognostic or predictive test. In deliberating barriers to clinical implementation, we review pitfalls associated with transcriptomic profiling and illustrate a simple immunohistochemistry (IHC)‐based subtyping algorithm that may serve as a faster, less expensive alternative. Envisioned as a research tool that can easily be translated into routine pathology workflow, IHC‐based profiling has the potential to more rapidly establish the utility (or lack thereof) of cell type profiling in clinical practice. Copyright © 2019 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.